Bee-Friendly Native Seed Mixtures for the Greening of Solar Parks - Maren Helen Meyer; Sandra Dullau; Pascal Scholz; Markus Andreas Meyer; Sabine Tischew (Land, 2023)
Photovoltaics is one of the key technologies for reducing greenhouse gas emissions and achieving climate neutrality for Europe by 2050, which has led to the promotion of solar parks. These parks can span up to several hundred hectares, and grassland vegetation is usually created between and under the panels. Establishing species-rich grasslands using native seed mixtures can enhance a variety of ecosystem services, including pollination. We present an overall concept for designing native seed mixtures to promote pollinators, especially wild bees, in solar parks. It takes into account the specific site conditions, the small-scale modified conditions caused by the solar panels, and the requirement to avoid panel shading. We highlight the challenges and constraints resulting from the availability of species on the seed market. Furthermore, we provide an easy-to-use index for determining the value of native seed mixtures for wild bee enhancement and apply it as an example to several mixtures specifically designed for solar parks. The increased availability of regional seed would allow a more thorough consideration of pollinator-relevant traits when composing native seed mixtures, thereby enhancing ecosystem services associated with pollinators such as wild bees.